2013
DOI: 10.4236/abc.2013.36065
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular characterization of a novel <i>pseudomonas putida</i> strain capable of degrading organophosphate and aromatic compounds

Abstract: A bacterial strain designated in this study as POXN01 was found to be capable of degrading the synthetic organophosphorus pesticides paraoxon and methyl parathion. The strain was initially isolated through enrichment technique from rice field soil near Harlingen, Texas. Phylogenetic analysis based on 16S rRNA, gyrB and rpoD gene alignments identified the POXN01 isolate as a new strain of Pseudomonas putida, which is closely related to the recently discovered nicotine-degrading strain Pseudomonas putida S16. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…It should be noted that P . putida POXN01, other strain isolated from rice fields [ 52 ] as S16, has high relationship with strains clade I ( S1 Fig ). HB4184 and H8234 were found to be placed within a different clade, together with the fresh water isolate GB-1; protein identities of these strains were at least >80%.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that P . putida POXN01, other strain isolated from rice fields [ 52 ] as S16, has high relationship with strains clade I ( S1 Fig ). HB4184 and H8234 were found to be placed within a different clade, together with the fresh water isolate GB-1; protein identities of these strains were at least >80%.…”
Section: Resultsmentioning
confidence: 99%
“…These results showed that with increasing incubation time, concentration of the remaining of endosulfan pesticide decreased in culture tubes (Table 1). Organochlorine pesticides are utilized directly for agricultural farms or soil and can contaminate sewerage and ditches, which in turn may be transported to rivers, and when this substances are distributed in the environment they become a pollutant and require remediation (12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
“…Media for bacterial growth: carbon-deficient minimal medium (CSM) and Luria-Bertani Medium (LB) were prepared as described previously (OD 600 nm) (12). Immediately before inoculation, CSM was supplemented with different concentration (100, 200, 300, and 400 µg/ML) of endosulfan.…”
Section: Methodsmentioning
confidence: 99%
“…Degradation of organophosphate by resting cells: Degradation experiment of OP was performed as previously described by Lyer et al (23). Briefly, 150 mL of LB medium was inoculated with transfected P. plecoglossicida on a rotary shaker at 37°C with 200 rpm rotation until cell density reached 1.0 at OD = 600.…”
Section: Chemicalsmentioning
confidence: 99%
“…ATCC 27551; forward primer: CGCCACTTTCGATGCGAT; reverse primer: CTTCTAGACCAATCGCACTG (23). PCR program was as follows: 4.5 minutes at 94°C, 32 cycles at 94°C for 30 seconds, 55°C for 30seconds and 72°C for1 minute with a final elongation step at 72°C for 4 minutes.…”
Section: Amplification and Insertion Of Organophosphorus Hydrolase Gementioning
confidence: 99%